A Membrane Proximal Helix in the Cytosolic Domain of the Human APP Interacting Protein LR11/SorLA Deforms Liposomes - Gill, Richard L. (Biochim Biophys Acta, 2014)
Over the last decade, compelling evidence has linked the development of Alzheimer’s disease (AD) to defective intracellular trafficking of the amyloid precursor protein (APP). Faulty APP trafficking results in an overproduction of Aβ peptides, which is generally agreed to be the primary cause of AD-related pathogenesis. LR11 (SorLA), a type I transmembrane sorting receptor, has emerged as a key regulator of APP trafficking and processing. It directly interacts with APP and diverts it away from amyloidogenic processing. The 54-residue cytosolic domain of LR11 is essential for its proper intracellular localization and trafficking which, in turn, determines the fate of APP. Here, we have found a surprising membrane-proximal amphipathic helix in the cytosolic domain of LR11. Moreover, a peptide corresponding to this region folds into an α-helical structure in the presence of liposomes and transforms liposomes to small vesicles and tubule-like particles. We postulate that this amphipathic helix may contribute to the dynamic remodeling of membrane structure and facilitate LR11 intracellular transport.